EXPLAINING THE NEW RULES OF BMX CYCLING IN AN INDIVIDUAL WAY (BMX RACING) - Umarov, Sarvar Mirzhaxitovich (Educational Research in Universal Sciences, 2023)
This article provides an explanation of the rules and requirements for BMX racing cycling for all ages from the requirements for a bicycle to the regulation of participants in races.